Pequenas centrais hidrelétricas (PCHs): conceitos, normas e a PCH Malagone - Damasceno, Isabelle Aparecida (2014)
The debate about of Small Hydropower Plants (SHPs) if to justify as it is necessary to understand how this kind of hydropower production go if agglomeration in different regions of Brazil, which the discussion if based in appropriation more sustainable the natural assets for national progress. The goal is discussion through academic reading and legislative, the forward and rewind of main standards and issues governing about of subject, beyond the seek to understand how the reformulation normative to meet the wishes that investors, but otherwise promote the detriment that environment issues. Subsequently, proceeded to analysis of River Basin Paranaíba as general scenario of the actual and future overview progress of SHPs. From this analysis focused in state of Minas Gerais as political agent that acts more towards in order to ensure the production of energy, benefiting the entrepreneur than its population. Moreover, within this broad scenario, brings up some inserts of SHP Malagone in Uberlândia - MG as demonstrative scenario of changes caused by the massive hydroelectric option.